From “Dark Matter” to “Star”: Insight Into the Regulation Mechanisms of Plant Functional Long Non-Coding RNAs - Chen, Qingshuai; Liu, Kui; Yu, Ru; Zhou, Bailing; Huang, Pingping; Cao, Zanxia; Zhou, Yaoqi; Wang, Jihua (Frontiers in Plant Science, 2021)
Long non-coding RNAs (lncRNAs) play a vital role in a variety of biological functions in plant growth and development. Here we provide an overview of the molecular mechanisms of lncRNAs in interacting with other biomolecules with an emphasis on those lncRNAs validated by low-throughput experiments only. LncRNAs function through playing multiple roles, including sponger for sequestering RNA or DNA, guider or decoy for recruiting or hijacking transcription factors or peptides, and scaffold for binding with chromatin modification complexes, as well as precursor of microRNAs or small interfering RNAs. These regulatory roles have been validated in several plant species with a comprehensive list of 73 lncRNA-molecule interaction pairs in 16 plant species found so far, suggesting their commonality in the plant kingdom. Such initial discoveries of a small number of functional plant lncRNAs represent the beginning of what is to come as lncRNAs with unknown functions were found in orders of magnitude more than proteins.